Highly prevalent Russian HIV-1 V3-loop sequence variants are susceptible to maraviroc. (June 2021) - Lewis, ME; Jubb, B; Simpson, P; Lopatukhin, A; Kireev, D; Bobkova, M; Craig, C; van der Ryst, E; Westby, M; Butler, SL
Introduction: Maraviroc inhibits CCR5-tropic HIV-1 across different subtypes in vitro and has demonstrated efficacy in clinical trials. V3-loop amino acid variants observed in individual maraviroc-resistant viruses have not been found to be predictive of reduced susceptibility. Sequence-database searches have demonstrated that approximately 7.3% of viruses naturally encode these variants, raising concerns regarding potential pre-existing resistance. A study from Russia reported that combinations of these same amino acids are present in the V3 loops of the Russian variant subtype A (IDU-A, now A6) with a much greater prevalence (range: 74.4%–92.3%) depending on the combination. However, these studies and database searches did not include phenotypic evaluation. Methods: Sixteen Russian HIV-1 isolates (including sub-subtype A6 viruses) were assessed for V3 loop sequence and phenotypic susceptibility to maraviroc. Results: All 12 of the A6 viruses and 2/4 subtype B isolates encoded V3-loop variants that have previously been identified in individual virus isolates with reduced susceptibility to maraviroc. However, despite the prevalence of these V3-loop amino acid variants among the tested viruses, phenotypic sensitivity to maraviroc was observed in all instances. Similarly, reduced susceptibility to maraviroc was not found in virus from participants who experienced virologic failure in a clinical study of maraviroc in Russia (A4001101, [NCT01275625]). Discussion: Altogether, these data confirm that the presence of individual or combinations of V3-loop amino acid residues in sub-subtype A6 viruses alone does not predict natural resistance to maraviroc and that V3-loop genotype analysis of R5 virus prior to treatment is not helpful in predicting clinical outcome.